Effects of naringenin on the pharmacokinetics of tofacitinib in rats - Bo Wang; Jiquan Shen; Quan Zhou; Deru Meng; Youwu He; Feifei Chen; Shuanghu Wang; Weiping Ji (Taylor & Francis Group, 2020)
Context Naringenin and tofacitinib are often used together for treatment of rheumatoid arthritis in Chinese clinics. Objective This experiment investigates the effect of naringenin on the pharmacokinetics of tofacitinib in rats. Materials and methods Twelve Sprague-Dawley rats were randomly divided into two groups (experimental group and control group). The experimental group was pre-treated with naringenin (150 mg/kg/day) for two weeks before dosing tofacitinib, and equal amounts of CMC-Na solution in the control group. After a single oral administration of 5 mg/kg of tofacitinib, 50 μL blood samples were directly collected into 1.5 mL heparinized tubes via the caudal vein at 0.083, 0.5, 1, 2, 3, 4, 6, 8, 10, 12 and 24 h. The plasma concentration of tofacitinib was quantified by UPLC/MS-MS. Results Results indicated that naringenin could significantly affect the pharmacokinetics of tofacitinib. The AUC0-24 of tofacitinib was increased from 1222.81 ± 222.07 to 2016.27 ± 481.62 ng/mL/h, and the difference was significant (p < 0.05). Compared with the control group, the Tmax was increased from 0.75 ± 0.29 to 3.00 ± 0.00 h (p < 0.05), and the MRT(0-24) was increased from 4.90 ± 0.51 to 6.57 ± 0.66 h (p < 0.05), but the clearance was obviously decreased from 4.10 ± 0.72 to 2.42 ± 0.70 L/h/kg (p < 0.05) in experimental group. Although the Cmax and t1/2 of tofacitinib were increased, there were no significant differences (p > 0.05). Conclusions This research demonstrated a drug-drug interaction between naringenin and tofacitinib possibly when preadministered with naringenin; thus, we should pay attention to this possibility in the clinic.